Exploring the importance of B2B relationship quality on customer loyalty: a study of the Chinese SaaS industry - Chunyan, Li (2022)
B2B relationship quality plays a crucial role in managing customer loyalty. It is crucial to understand the antecedents of the three fundamental dimensions of B2B relationship quality, namely trust, commitment and satisfaction, and to explore in depth the processes by which they influence the management of customer loyalty. In the prior literature, scholars have focused on the buyers when examining the impact of B2B relationship quality on customer loyalty, with limited relevant research on the sellers. Meanwhile, prior literature has focused on the causal relationship between B2B relationship quality and loyalty, while the analysis of the process of how to build high-quality B2B relationships and promote customer loyalty is lacking. Therefore, this study aims to explore the importance of B2B relationship quality and how it can be enhanced to enhance customer loyalty. To further validate whether buyers and sellers share the same perceptions of relationship quality in the B2B context, this study will include both sellers and buyers in a business relationship. In terms of research methodology, the complexity involved in B2B relationship quality and the complex relationship between relationship quality and customer loyalty requires the use of rich data and interviews for further research. Therefore, this study primarily uses semi-structured interviews for qualitative research by examining the perspectives of sellers and buyers in a B2B environment to gain a more detailed understanding of how trust, commitment and satisfaction in B2B relationship quality play a role in managing B2B customer loyalty. A thematic analysis was also used to code the interview data, grouping first-order themes, second-order themes and overall dimensions. On top of this, themes were correlated with the literature and findings were analysed and discussed. Four components were eventually identified: (1) High- quality relationships bring business value to B2B partnerships, (2) Enhanced trust between B2B buyers and sellers to achieve B2B customer loyalty, (3) Arising commitment and its impact on B2B customer loyalty, (4) The maintenance of high and continuous satisfaction on B2B customer loyalty. This study explores in depth how to build high-quality B2B relationships to promote customer loyalty by examining buyer and seller perspectives on B2B relationship quality and customer loyalty.